Length-weight relationships and condition factors of three fish species in the Karamenderes Stream (Çanakkale, Türkiye) - Şükran Yalçın Özdilek; Nurbanu Partal (Turkish Journal of Bioscience and Collections)
Objective: The aim of this study is to determine the length-weight relationships and condition factors of two native freshwater fish species and the invasive Carassius gibelio in the Karamenderes Stream (Çanakkale, Türkiye). Materials and Methods: Fish specimens were caught monthly from August 2007 to July 2008 using cast nets in Karamenderes Stream’s Pınarbaşı location. The length-weight relationship was calculated according to W = aLb and the Fulton’s condition factor was calculated according to K = 100*W/L3 equations. Results: The b (slope) values of the length-weight relationships are 3.026, 3.201, and 3.255, respectively, for Barbus oligolepis, Squalius cii, and C. gibelio. The growth was isometric in B. oligolepis and positive allometric in C. gibelio and S. cii. The Fulton’s condition factor varied between 0.51 and 2.08 in C. gibelio, 0.76 and 1.25 in B. oligolepis, and 0.59 and 1.44 in S. cii specimens. Conclusion: This study is the first report that presents the length-weight relationship of two native species, B. oligolepis and S. cii, in the presence of invasive C. gibelio. The length and weight distribution pattern through the year indicated that there was seasonality in the utilization of this section of the stream by juvenile and adult stages of three species. The lowest condition factor and b value in B. oligolepis led us to the conclusion that the competitive exclusion risk of this species. The effect of invasive C. gibelio on the natives should be further researched focusing on species interactions. From the fact that there are limited data on the length-weight relationship and biology of B. oligolepis and S. cii, there is a need for further research.